Consciousness transitions : phylogenetic, ontogenetic and physiological aspects. - Liljenström, Hans, 1956-; Århem, Peter, 1946- (Elsevier Science, 2008)
It was not long ago when the consciousness was not considered a problem for science. However, this has now changed and the problem of consciousness is considered the greatest challenge to science. In the last decade, a great number of books and articles have been published in the field, but very few have focused on the how consciousness evolves and develops, and what characterizes the transitions between different conscious states, in animals and humans. This book addresses these questions. Renowned researchers from different fields of science (including neurobiology, evolutionary biology, ethology, cognitive science, computational neuroscience and philosophy) contribute with their results and theories in this book, making it a unique collection of the state-of-the-art of this young field of consciousness studies. - First book on the topic - Focus on different levels of consciousness, including: Evolutionary, developmental, and functional - Highly interdisciplinary.